Investigação do efeito ansíolitico-símile e antidepressivo-sí-mile do monoterpeno tetrahidrolinalol por meio de abordagens in silico e in vivo - Silva, Pablo Rayff da (2023)
Pharmacological therapeutic approaches to treat anxiety and depression focus on the modula-tion of neurotransmission systems involved in their neurobiology – catecholaminergic, glu-tamatergic, and oxidonitrergic pathways stand out. Among the available treatments, aromatic plants stand out as an important therapeutic resource, and their chemical constituents (e.g., monoterpenes) are being studied in the search for new treatments for anxiety and depression. Therefore, the aim of this study was to evaluate the acute toxicity as well as the anxiolytic-like and antidepressant-like potential of the monoterpene tetrahydrolinalool (THL) through in silico and in vivo models. Initially, oral treatment with THL at doses of 300 and 2000 mg/kg-1 showed low toxicity with an estimated LD50 ranging from 2000 to 5000 mg/kg-1. In addition, behavioral tests were performed in mice treated with THL (37.5-600 mg/kg-1, p.o.) using the elevated plus maze (EPM), open field (OF), rotarod (RR), and forced swim (FS) tests. Consequently, THL at doses of 37.5 and 75 mg/kg-1 induced a significant increase in the number of entries (72.7% and 64.3%, respectively) and time spent (80.3% and 76.8%, respectively) by the animals in the open arms of the elevated plus maze. However, higher doses of the compound 300 and 600 mg/kg-1) reduced the number of crossings made by the animals in the OF 30.6 % and 31.6% %, respec-tively) but did not alter their motor coordination in the RR. In the FS test, treatment with the monoterpene significantly reduced the immobility time of mice at doses of 150, 300, and 600 mg/kg-1 by 69.3%, 60.9%, and 68.7%, respectively. In molecular docking assays, THL showed satisfactory energy values compared to co-crystallized ligands for the following targets: nNOS, GCs, IL-6, 5-HT1A, NMDAr, and D1. These results were confirmed using in vivo tests, which demonstrated antagonism of the antidepressant-like effect of the monoterpene by SCH, an en-antioselective D1 antagonist. In addition, the antidepressant-like effect of THL was potentiated by ketamine, an NMDA receptor antagonist, and by methylene blue, a GCs/NO inhibitor. The latter effect was accompanied by a reduction in nitrite levels in the cortex and hippocampal structures of treated mice. Finally, the compound showed good absorption and high bioavaila-bility in silico. Taken together, the results indicate that THL is a nontoxic monoterpene, accord-ing to the protocols used. It shows good oral bioavailability and possesses a sedative effect at high doses, as well as anxiolytic- and antidepressant-like effects that appear to depend, at least in part, on dopaminergic, glutamatergic, and oxidonitrergic neurotransmission systems.